Natural organic matter coagulation - Sharp, Emma (Cranfield University, 2005)
The removal of natural organic matter (NOM) is one of the main challenges facing water utilities in both the UK and the US. As a consequence of changes in land management and an increased carbon loss from solids, a greater amount of accumulated organics is now being flushed into the aquatic environment during increased surface run-off events such as snowmelt or heavy rainfall. Furthermore, whilst traditional treatment with trivalent coagulants has proven a successful strategy in the past, operational problems are now being reported during periods of elevated organic levels in the water. These include the formation of fragile flocs, a greater particulate carryover onto downstream processes and increased disinfection by product (DBP) formation. Resin adsorption techniques were employed to fractionate the water samples into their hydrophobic and hydrophilic components. This, coupled with raw water monitoring, revealed that NOM composition and characteristics can vary, even if the total organic concentrations appear stable. In particular, hydrophobic NOM fractions contribute the majority of the charge compared to the hydrophilic fractions, and therefore exert a greater impact on coagulation conditions. Comparison across different source waters, seasons, at varying experimental scales and under varying coagulation conditions, revealed that zeta potential monitoring during coagulation takes into account the changing electrical property of the water, and in general, maintaining a value between -10<ζ<+3 mV will result in low and stable residuals. A similar operational zeta potential range exists for clarification processes, although the zeta potential value at the positive threshold is influenced by the hydrophobic NOM content, such that the range is extended as the specific UV absorbance (SUVA) value of the raw water decreases. Whereas the hydrophilic concentration was found to control the achievable dissolved organic carbon (DOC) residual, attributed to a negligible charge density and poor coagulant-interactions. Consequently, the key finding of this study is that raw water characterisation coupled with zeta potential monitoring will provide a straightforward guide to the mechanistic understanding of treating NOM rich waters.